Development and In-House Validation of an LC–MS and LC–MS/MS Assay for the Determination of Food Fraud for Different Fish Species. (3rd December 2019) - Lasch, Philipp; Uhlig, Steffen; Uhlig, Carsten; Wilhelm, Christian; Bergmann, Nicola; Wittke, Stefan
Abstract: Background: Fish and fish products are one of the most important food sources of high commercial interest. The global food trade and the associated risks are constantly presenting new challenges to consumer protection and public authorities, which, among other things, demand state-of-the-art analytical methods to ensure food authenticity. Objective: The establishment of MS-based strategies plays a decisive role alongside the (further) development of ELISA- or DNA-oriented methods. Methods: In the present work, therefore, the development and in-house validation of an LC–MS and LC–MS/MS-based assay for authenticity testing of certain fish species is described. Results: Based on the execution of a validated bottom-up LC–electrospray–MS and MS/MS assay and multivariate analysis, the commercially available species Lutjanus malabaricus (red snapper) and Sebastes spp. (redfish) are distinguished from each other, whereas an additional 68 samples [nine additional marine species such as pangasius ( Pangasianodon hypophthalmus ), salmon ( Salmo salar ), turbot ( Scophthalmus maximus ), plaice ( Pleuronectes platessa ), sole ( Solea solea ), lemon sole ( Glyptocephalus cynoglossus ), halibut ( Reinhardtius hypoglossoides ), red salmon ( Oncorhynchus nerka ), and great scallop ( Pecten jacobaeus )] served as blinded negative controls to ensure the specificity of the assay. Conclusions and Highlights: A promising LC–MS and LC–MSMS based assay has been developed that could enable the detection of fish fraud at the protein level in the future.